1999
DOI: 10.1115/1.2841303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hole Length-to-Diameter Ratio on Film Cooling With Cylindrical Holes

Abstract: Film cooling experiments were conducted to investigate the effects of coolant hole length-to-diameter ratio on the film cooling effectiveness. The results from these experiments offer an explanation for the differences between the film cooling results for cylindrical hole injection configurations previously reported by Goldstein et al. (1974), Pedersen et al. (1977), and Sinha et al. (1991). The previously reported injection configurations differed primarily in coolant hole length-to-diameter ratio. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…The inclination angle (α) was 35°, the compound angle (β) was 0°, and the L/D was 8. A higher L/D reduces the premature lift-off [9] . The p/D was maintained at 3 for the 5 film cooling holes.…”
Section: B Secondary Flowmentioning
confidence: 98%
See 1 more Smart Citation
“…The inclination angle (α) was 35°, the compound angle (β) was 0°, and the L/D was 8. A higher L/D reduces the premature lift-off [9] . The p/D was maintained at 3 for the 5 film cooling holes.…”
Section: B Secondary Flowmentioning
confidence: 98%
“…Some of the investigations on flat plate with streamwise inclination of discrete holes were performed by Eriksen and Goldstein [1], Goldstein et al [2] , Goldstein and Yoshida [3] , Sinha et al [4] , Bell et al [5] , Hay et al [6] , Liess [7] , Pedersen et al [8] , Lutum and Johnson [9], Goldstein and Taylor [10] , and Amari et al [11] . The effects of film hole geometry and density ratio were studied by Goldstein et al [2] .…”
Section: Review Of Literaturementioning
confidence: 98%
“…They investigated the influence of a plenum on film cooling and found that the plenum geometry has an effect on the film cooling effectiveness, which depends on the injection hole length and streamwise hole angle. The effect of the hole length in the film cooling process was demonstrated in the study of Lutum and Johnson (1998). They reported that the length to diameter ratio larger than 7, has a small effect on the film cooling effectiveness.…”
Section: Introductionmentioning
confidence: 96%
“…Some of the most important parameters which have gained much of the researchers' attention are: cooling jet injection angle [6], compound injection angle [7,8], blowing ratio [9,10], spanwise and streamwise hole spacing [11,12], length of the cooling jet [13,14,15,16,17,18], boundary layer thickness [19], convexity or concavity of the wall [19], and turbulence [15,20,21,22].…”
Section: Introductionmentioning
confidence: 99%